Zoogeography of Termites of North-western Himalayan Region - Thakur, M. L. (Indian Forester, 1975)
North-Western Himalayan Region has been the subject of much extensive explorations for insect collections. However, very little attention has been paid for the study of termite fauna of this region. The author, in collaboration with P. N. Chatterjee (1-3) published a comprehensive systematic account of North-Western Himalayan termite fauna, recording 10 genera and 18 species. In the present contribution, it is endeavoured to discuss the zoogeographical considerations of termite fauna. The fauna of this region is largely Indo-Malayan and show continuity with the Gangatic Plain (Indian sub-region, above 20 Â°lat). Four of the eight families of living termites are present and of these, family Termitidae constitute the major component of the fauna (72.2%). In the family Termitidae, sub-family Macrotermitinae dominates and is represented by nine species (50%). The sub-family Nasutitermitinae, the most highly evolved sub-family is totally absent. The most successful genus Odonlotermes Holmgern is represented by seven species (38.9%). The other notable component is the relic genus Archotermopsis, which is represented by two species. The remaining genera are represented by single species each. Thus, the North Western Himalayan termite fauna is rich in genera. But poor in species. It has been further, observed that with the rise in altitude, there is a sharp decline in the number of genera and species. This is in conformity with the known distribution pattern of termites. The low percentage of endemism (33.32%) and paucity of species in general is suggestive of its less suitability as a natural habitat for termite.